2021
DOI: 10.1039/d0sc07045a
|View full text |Cite
|
Sign up to set email alerts
|

Metallofullerene photoswitches driven by photoinduced fullerene-to-metal electron transfer

Abstract: We report on the discovery and detailed exploration of the unconventional photo-switching mechanism in metallofullerenes, in which the energy of the photon absorbed by the carbon cage π-system is transformed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…It should be noted that the emission spectra of fullerenes and metallofullerenes have a complex vibronic structure. Similar to the case of Y 3 N@C 80 , the peak intensity of the vibronic band near 740 nm of DyY 2 N@C 80 increases from 300 to 100 K. With temperature further cooling down from 100 to 80 K, TADF peak of DyY 2 N@C 80 starts to decrease due to the reduced RISC efficiency, and a certain phosphorescence peak near 740 nm appears and coincides with a vibronic band from 100 to 80 K . Briefly, TADF is activated when the temperature increases from 80 to 100 K for DyY 2 N@C 80 .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…It should be noted that the emission spectra of fullerenes and metallofullerenes have a complex vibronic structure. Similar to the case of Y 3 N@C 80 , the peak intensity of the vibronic band near 740 nm of DyY 2 N@C 80 increases from 300 to 100 K. With temperature further cooling down from 100 to 80 K, TADF peak of DyY 2 N@C 80 starts to decrease due to the reduced RISC efficiency, and a certain phosphorescence peak near 740 nm appears and coincides with a vibronic band from 100 to 80 K . Briefly, TADF is activated when the temperature increases from 80 to 100 K for DyY 2 N@C 80 .…”
Section: Resultsmentioning
confidence: 69%
“…This phenomenon further demonstrates that Dy 3+ greatly influences the temperature-dependent photoluminescence of the Y 3+ -coordinated C 80 cage. Notably, the introduction of Sc 3+ ions in Y x Sc 3– x N@C 80 ( x = 0–3) also affects the photoluminescence of the Y 3+ -coordinated carbon cage, because structural reorganizations of endohedral clusters of metallofullerenes caused by charge transfer between endohedral clusters and carbon cage upon excitation affect the photoluminescence wavelength . The more obvious shift of the TADF peak and the peak near 740 nm for DyY 2 N@C 80 compared to Y 3 N@C 80 upon varying temperatures indicates that the introduction of Dy 3+ may induce a stronger interaction between the carbon cage and the endohedral cluster.…”
Section: Resultsmentioning
confidence: 99%
“…S10 †). 111 This surprising finding was then confirmed by LDI-TOF mass-spectrometry analysis, which revealed a small signal of Y 2 ScN@C 80 when the measurements were performed with strongly increased laser power; under our standard LDI-TOF measurement conditions, this signal was not detectable (Fig. S11 †).…”
Section: Photoluminescence Of Dyy 2 N@c 80mentioning
confidence: 58%
“…On the photoluminescence of DyY 2 N@C 80 . Our earlier finding of thermally-activated delayed fluorescence (TADF) in the series of Y x Sc 3−x N@C 80 EMFs (x = 0-3) 111,112 suggested that similar phenomena may be present in other M 3 N@C 80 molecules. Indeed, TADF was recently reported in DyY 2 N@C 80 .…”
Section: 𝑈 Effmentioning
confidence: 87%
“…A previous electrochemical study of a series of Sc x Y 3– x @C 80 ( x = 0–3) has shown that the reduction is positively shifted from −1.37 to −1.24 V as the number of x increased, namely, the number of Sc atoms in C 80 . Per se, this is reflected in the LUMO lowering by Sc. , For the Sc 3 N@C 80 -dumbbell, the increasing contribution (∼1%) of the Sc 3d-orbital to the LUMO should originate from the electronic communications between the two Sc 3 N clusters, which in turn lower the LUMO level by 0.038 eV. This, in turn, is comparable to the change of redox potential when increasing the number of Sc in the Sc x Y 3‑x @C 80 series.…”
mentioning
confidence: 95%